THE EFFECT OF USING SCRABBLES ON THE STUDENTS’ VOCABULARY ACHIEVEMENT IN GRADE VII AT SMP SINAR-HARAPAN - Ewin Pasaribu and Lince Sihombing (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
The objective of this study was to find out the effect of using Scrabbles on Students’ Vocabulary Achievement. It was conducted by using experimental research design. The population of this study was the Seventh Grade students of SMP Sinar Harapan (72) the class sample (VII2) was taken purposively and divided into two smaller classes. The data collection in this study was done by giving multiple choice tests. The material was texts about mass communication and they were being informed to the students in two ways, by using scrabbles and non-scrabbles. Pre-test and post-test were administered to find out the score of every student. The scores were being calculated into mean classes and analyzed by using t-test formula. The analysis result of this study showed that experimental group (Scrabbles Learning Class) has reached better result which was indicated by the mean 73,125 (mean of Experimental Group) compared to 63, 375 (mean of Control Group). Statistically the result of both groups after being tested by t-test formula shows that tobs 5,065 is higher than ttable 2.088 (tobs 5, 065 > ttable 2.088), this concluded that Ho is Rejected and Ha is Accepted.